Ready-to-use violence prevention skills lessons and activities for secondary students - Begun, Ruth Weltmann,; Huml, Frank J., (Center for Applied Research in Education, 1998)
Life skills: making proper decisions; learning to be tolerant; responding to failure; learning to cope with life's problems by using social skills. Respect: developing self-respect; dealing with disrespect. Relationships: developing communication skills; establishing a good relationship; resolving conflicts peacefully... Anger. Family. Stress and danger. Suicide. Stimulants. Crime.